2015
DOI: 10.1038/ncomms8647
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically stretchable and transparent thin-film transistors based on printable silver nanowires, carbon nanotubes and an elastomeric dielectric

Abstract: Thin-film field-effect transistor is a fundamental component behind various mordern electronics. The development of stretchable electronics poses fundamental challenges in developing new electronic materials for stretchable thin-film transistors that are mechanically compliant and solution processable. Here we report the fabrication of transparent thin-film transistors that behave like an elastomer film. The entire fabrication is carried out by solution-based techniques, and the resulting devices exhibit a mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
271
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(274 citation statements)
references
References 45 publications
1
271
0
Order By: Relevance
“…[197] It is also possible to achieve much better mechanical stability if using elastomeric materials as the substrate and dielectric. [198] Xia et al reported a stretchable all-CNT transistor with an elastomeric polydimethylsiloxane (PDMS) thin film as substrate and dielectric layer, showing no noticeable change (less than 5%) in electrical performance up to a large strain of 22.5%. [199] Chortos et al selected a tough thermoplastic polyurethane (TPU) as the dielectric and substrate to fabricate transparent and stretchable all-CNT TFTs (Figure 9), where the channel and electrodes consisted of polymer-sorted and unsorted CNTs, respectively.…”
Section: Carbon Nanotubes As Electrodesmentioning
confidence: 99%
“…[197] It is also possible to achieve much better mechanical stability if using elastomeric materials as the substrate and dielectric. [198] Xia et al reported a stretchable all-CNT transistor with an elastomeric polydimethylsiloxane (PDMS) thin film as substrate and dielectric layer, showing no noticeable change (less than 5%) in electrical performance up to a large strain of 22.5%. [199] Chortos et al selected a tough thermoplastic polyurethane (TPU) as the dielectric and substrate to fabricate transparent and stretchable all-CNT TFTs (Figure 9), where the channel and electrodes consisted of polymer-sorted and unsorted CNTs, respectively.…”
Section: Carbon Nanotubes As Electrodesmentioning
confidence: 99%
“…The most widely explored schemes involve NWs, where there are many examples of flexible/ stretchable electronics that exploit the outstanding electrical, 39 mechanical, 40 and optical properties 41 of these materials. In one representative case, hydro-thermal growth of vertically oriented ZnO NWs yields active materials for adaptive tactile imaging systems, as shown in Fig.…”
Section: Bottom-up Approachesmentioning
confidence: 99%
“…Although intrinsically stretchable circuit elements, such as transistors,5 capacitors,6 and light‐emitting electrochemical cells,[[qv: 2b]] have been developed, these components will not be able to match the performance of their rigid counterparts. Therefore, many stretchable electronic applications will require the mounting of rigid components onto stretchable circuit boards (SCBs), where the SCB accounts for the mechanical deformation of the system.…”
mentioning
confidence: 99%